2021
DOI: 10.1002/pssa.202000672
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Biomimetic Deposition of Calcium Phosphate in Real Time Using Complex Capacitance

Abstract: Deposition of minerals, particularly calcium phosphates such as hydroxyapatite, is an important process in the formation of hard tissues such as bone. Herein, a new, affordable, straightforward and nondestructive method based on complex capacitance spectroscopy, an application of electrochemical impedance spectroscopy, is described which allows repeated and real‐time measurements of the same sample throughout the calcium phosphate deposition process. In contrast with end‐point assays which require large number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…On the other hand, a closer-to-amorphous apatitic phase in the case of CaSrZnP1.67-BS was detected. The SEM characterization ( Figure 9B ) showed that the new CaPs formed on the surface of microparticles has morphologies previously observed in (biomimetic) CaPs formed in simulated body fluids ( Barradas et al, 2013 ; Guttenplan et al, 2021b ). No specific trends in the surface roughness levels could be observed ( Supplementary Figure S5 ).…”
Section: Resultssupporting
confidence: 60%
“…On the other hand, a closer-to-amorphous apatitic phase in the case of CaSrZnP1.67-BS was detected. The SEM characterization ( Figure 9B ) showed that the new CaPs formed on the surface of microparticles has morphologies previously observed in (biomimetic) CaPs formed in simulated body fluids ( Barradas et al, 2013 ; Guttenplan et al, 2021b ). No specific trends in the surface roughness levels could be observed ( Supplementary Figure S5 ).…”
Section: Resultssupporting
confidence: 60%
“…Though redoxless EIS has been common in corrosion research, it has received less attention from biosensor researchers. A few researchers have attempted to apply redoxless EIS or ECS to the investigation of the dielectric properties of self-assembled monolayers (SAMs) [28], biomimetic deposition of calcium phosphate [29], and direct detection of lead ions in tap water [30]. Recently, redoxless impedimetric methods have been applied to biochemical analysis, including the detection of ions [31], D-dimers [32], and low-molecular-weight triamterene [33].…”
Section: Introductionmentioning
confidence: 99%